Peran Pemimpin Dan Komunikasi Interpersonal Dalam Penerapan Aplikasi Simponi ASN Di Dinas Perhubungan Provinsi Sulawesi Tenggara - Asriyati Asriyati; Maudhy Satyadharma (Politeknik Kampar, 2023)
The Research was conducted at the Department of Transportation of Southeast Sulawesi Provincial to analyze the role of leaders and interpersonal communication in supporting the successful implementation of the Simponi ASN Application. The approach used in this research is a qualitative descriptive approach. The data collection techniques used in this research were interviews, observation and documentation studies. The informant selection technique used was purposive sampling. The data analysis technique used an interactive analysis model consisting of data collection, data reduction, data presentation and drawing conclusions. The research results found that success in implementing the ASN Simponi Application within the Department of Transportation of Southeast Sulawesi Provincial was supported by leadership factors and effective interpersonal communication.